Implementation of Character Education through Scout Extracurricular Activities at Ma'arif Nurul Jannah Elementary School - Ansori, Tri Ahmad; An-Nisa, Apriani; Harwati, Tantri (Journal of Islamic Education and Ethics, 2024)
This research was conducted to find out the implementation of character education at Ma`arif Nurul Jannah Elementary School. This is done because character education is the foundation for realizing the golden generation in the future and avoiding the events of moral decadence that are currently rife. This type of research is qualitative research. The data collection strategy in this study was conducted through interviews, observations, and documentation. The subjects incorporated in this study are the principal, class teachers, 9 scout coaches, and students who are members of scout activities. The data evaluation strategy used in this research is information reduction, information presentation, and conclusion drawing. The consequences of the research on the implementation of character education through extracurricular scouting at SD Ma'arif Nurul Jannah show that it is carried out together by marching, camping, exploring, and training. The application of character education in scout activities is carried out by 1) Making activity planning seen from the Daily Activity Journal by placing character values and the Activity Budget Plan. 2) Implementation of character education implementation on students who are members of scout activities every Friday. 3) Evaluation is carried out on students who are members of scout activities by means of periodic assessments when stopping training and coordination meetings for scout training. This is to find out how far the development has gone. The implementation of coaching scout extracurricular activities for students who are members is supported by the existence of policies or rules at school. There are scout coaches, the provision of investment centers or pick-up cars, large school yards, loudspeakers and some scout equipment. However, there are several obstacles in the implementation of scout activities to implement character education at SD Ma'arif Nurul Jannah, namely constrained funds, lack of uncertified scout coaches, and lack of support from parents.